PERAN E-GOVERNANCE SEBAGAI INSTRUMEN PENINGKATAN TRANSPARANSI DAN AKUNTABILITAS PEMERINTAHAN DI INDONESIA - Shabihah, Sierra Aulia; Ryanindityo, Mochammad; Nurkumalawati, Intan (Journal of Administration and International Development, 2025)
Digital transformation in government through e-governance is an important step in supporting bureaucratic reform and realizing good governance. This research aims to analyze the strategic role of e-governance in improving government transparency and accountability in Indonesia. Using qualitative methods through literature studies and case studies, this research examines various e-governance implementations in various regions. The results show that e-governance plays a strategic role in improving government transparency and accountability, which are the two main pillars in realizing good governance. The implementation of Electronic-Based Government System (SPBE) in a number of regions such as Ciamis Regency, Bandung City, and DKI Jakarta has a positive impact on access to public information, service efficiency, and citizen participation. Digital innovations such as the “Helo Ciamis” application, the ‘JAKI’ platform, and the “Open Data Jakarta” program have proven to encourage information disclosure and strengthen public oversight of government performance. However, the implementation of e-governance still faces challenges in the form of limited technological infrastructure, low public digital literacy, and resistance to change from bureaucratic apparatus. Thus, alignment between national policy and implementation at the local level is needed, increasing the capacity of human resources and strengthening public participation.